Inscriptions of Nature : Geology and the Naturalization of Antiquity - Chakrabarti, Pratik (Book collections on Project MUSE., 2020)
"This theoretical book is a work of history and of cultural studies. Through analyses of Gondwana, India, and its geological, anthropological, and cultural histories, the book describes how human evolution, mythological geographies, tribal aboriginality, and colonial state formation fundamentally defined India's antiquity"--